Pendampingan Penggunaan Media WhatsApp Bagi Usaha UMKM di Kota Wamena - Haryati, Tati; Siska, Defran; Ahmad, Ahmad; Ganggut, Fortunatus (Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
This service activity aims to increase the digital capacity of grocery kiosk MSME players in Wamena City through training and assistance in using WhatsApp Business as a means of promotion, communication, and customer service. The method used combines inductive, Asset-Based Community Development (ABCD), and Participatory Action Research (PAR) approaches, with gradual implementation starting from needs identification, training, to evaluation. Results showed that the majority of participants successfully activated and utilized WhatsApp Business features, including product catalogs, automated messages, and customer labels. The application improved service professionalism and expanded the market reach of MSMEs. Despite challenges such as limited internet and devices, the participatory approach and intensive mentoring were able to overcome these obstacles. This program proves the effectiveness of simple technology in supporting the digital transformation of MSMEs in disadvantaged areas in a sustainable manner.